Distinct high-energy cutoff variation patterns in two Seyfert galaxies. Issue 1 (8th January 2021) - Kang, Jia-Lai; Wang, Jun-Xian; Kang, Wen-Yong
ABSTRACT: Investigating how the cut-off energy E cut varies with X-ray flux and photon index Γ in individual active galactic nuclei (AGNs) opens a new window to probe the yet unclear coronal physics. So far E cut variations have only been detected in several AGNs but different patterns have been reported. Here, we report new detections of E cut variations in two Seyfert galaxies with multiple Nuclear Spectroscopic Telescope Array ( NuSTAR ) exposures. While in NGC 3227 E cut monotonically increases with Γ, the E cut –Γ relation exhibits a Λ shape in SWIFT J2127.4+5654 ( E cut increasing with Γ at Γ ≲ 2.05, but reversely decreasing at Γ ≳ 2.05), indicating more than a single underlying mechanism is involved. Meanwhile both galaxies show softer spectra while they brighten in X-ray, a common phenomenon in Seyfert galaxies. Plotting all seven AGNs with E cut variations ever reported with NuSTAR observations in the E cut –Γ diagram, we find they could be unified with the Λ pattern. Although the sample is small and SWIFT J2127.4+5654 is the only source with Γ varying across the break point thus the only one exhibiting the complete Λ pattern in a single source, the discoveries shed new light on the coronal physics in AGNs. Possible underlying physical mechanisms are discussed.